Mapping human genetic diversity in Asia - Abdulla, Mahmood Ameen; Ahmed, Ikhlak; Assawamakin, Anunchai; Bhak, Jong; Brahmachari, Samir K; Calacal, Gayvelline C; Chaurasia, Amit; Chen, Chien-Hsiun; Chen, Jieming; Chen, Yuan-Tsong; Chu, Jiayou; Cutiongco-de la Paz, Eva Maria C; et al. (Science (American Association for the Advancement of Science), 2009)
Asia harbors substantial cultural and linguistic diversity, but the geographic structure of genetic variation across the continent remains enigmatic. Here we report a large-scale survey of autosomal variation from a broad geographic sample of Asian human populations. Our results show that genetic ancestry is strongly correlated with linguistic affiliations as well as geography. Most populations show relatedness within ethnic/linguistic groups, despite prevalent gene flow among populations. More than 90% of East Asian (EA) haplotypes could be found in either Southeast Asian (SEA) or Central-South Asian (CSA) populations and show clinal structure with haplotype diversity decreasing from south to north. Furthermore, 50% of EA haplotypes were found in SEA only and 5% were found in CSA only, indicating that SEA was a major geographic source of EA populations.